Essentials of social emotional learning (SEL) the complete guide for schools and practitioners - Black, Donna (Psychologist) (Essentials of psychological assessment series, 2022)
"Educational learning environments will benefit most from the book as it explains and illustrates the significance of SEL, not simply as a program from a shelf, but rather as a school-wide effort that reshapes the learning environment into a positive, accepting, and socially just environment where students feel safe and valued, where outcomes are improved, and where communities are contributing partners. Using a "whole child" approach, readers will learn about a changing mindset toward education that prepares children and adolescents for more than test-taking success, but also for life-time learning. The book will address prevalent issues in the research, how to address the challenges and barriers associated with integrating SEL into everyday aspects of the curriculum and learning routines. The uniqueness/specialty of this book can be found in its approach to SEL. It will appeal to readers by helping them better understand the complexities of SEL as a process that must be individualized for each school/community. Readers will learn that SEL can't be sold as a packaged product -- it is not simply an "instructional program" that is taught for 20 minutes a day. Not only does this place the full burden and accountability on the instructional staff, it also is not sustainable. This book will explore how SEL is not a "one size fits all" model, but is an ongoing process that is unique to each learning environment, whether it's a school-wide environment, a classroom, environment, or an individual environment. In addition, it is a process that recognizes the uniqueness of the school community and its members."-- Provided by publisher.